Copper foil, electrodes containing the same, and secondary batteries

KR103032576B1Active Publication Date: 2026-10-13SK NEXILIS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020250057672
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-04-30
Publication Date
2026-10-13
Estimated Expiration
2045-04-30

Smart Images

  • Figure 112025049533320-PAT00015_ABST
    Figure 112025049533320-PAT00015_ABST
Patent Text Reader

Abstract

The present invention provides a copper foil comprising a copper film containing a metal chelating agent, wherein the △CTE according to Formula 1 below is 10 μm / (m·℃) or less, an electrode comprising the same, and a secondary battery. [Equation 1] △CTE = CTE2 - CTE1 In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a copper foil, an electrode containing the same, and a secondary battery. Background Technology

[0003] Rechargeable batteries are widely used as energy storage devices in various portable devices, electric vehicles, and energy storage systems (ESS). In particular, as high energy density and high power characteristics are simultaneously required, advanced technological development regarding electrode structures and constituent materials is continuously underway.

[0004] Generally, the cathode is formed by applying a slurry composed of an active material, a binder, and a conductive material to a current collector, followed by drying and roll pressing processes. Copper foil, which has excellent electrical conductivity and is easy to process, is widely used as the current collector.

[0005] Recently, as the demand for higher density and thinner electrodes has increased, design conditions such as increased active material coating, improved electrode density, and reduced electrode thickness are becoming increasingly sophisticated. Consequently, various performance requirements, including mechanical durability, process adaptability, surface precision, and coating uniformity, are being simultaneously imposed on copper foils.

[0006] In particular, when manufacturing electrodes, copper foil is repeatedly subjected to high-pressure roll presses and compressive loads of active materials, which can lead to various process problems such as reduced mechanical stability, wrinkling, tearing, softening, and surface defects.

[0007] Therefore, as electrode manufacturing conditions become more advanced, research is actively being conducted to optimize multifaceted characteristics such as copper foil thickness, crystal structure, surface roughness, chemical stability, and residual stress. The problem to be solved

[0009] The present invention provides a copper foil in which the coefficient of thermal expansion of the copper foil is stably maintained in different temperature ranges and mechanical properties and battery characteristics are improved, an electrode including the same, and a secondary battery. means of solving the problem

[0011] The copper foil according to the present invention comprises a copper film containing a metal chelating agent, and the △CTE according to Formula 1 below may be 10 μm / (m·℃) or less.

[0012] [Equation 1]

[0013] △CTE = CTE2 - CTE1

[0014] In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.

[0015] In one embodiment of the present invention, the CTE1 may be 15 μm / (m·℃) ± 1 μm / (m·℃).

[0016] In one embodiment of the present invention, the thermal expansion change rate index according to the following Equation 2 may be 0.6 or less.

[0017] [Equation 2]

[0018] Thermal expansion rate of change index = △CTE / CTE1

[0019] In the above Equation 2, △CTE and CTE1 are as defined in the above Equation 1.

[0020] In one embodiment of the present invention, the thermal expansion stability index according to the following Equation 3 may be 3 or less.

[0021] [Equation 3]

[0022] Thermal expansion stability index (units omitted) =

[0023] In the above Equation 3, the X iis CTE1, CTE2, CTE3, CTE4, or CTE5, where μ is the average of CTE1 to CTE5, n is 5, and CTE1 and CTE2 are as defined in Equation 1, and The above CTE3 is the third coefficient of thermal expansion of the copper foil measured by increasing the temperature from 40°C to 50°C under the same conditions, the above CTE4 is the fourth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 50°C to 60°C under the same conditions, and the above CTE5 is the fifth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 60°C to 70°C under the same conditions.

[0024] In one embodiment of the present invention, the CTE3, CTE4, and CTE5 may be 20 μm / (m·℃) ± 5 μm / (m·℃).

[0025] In one embodiment of the present invention, the copper foil comprises a protective film formed on at least one surface of the copper film, and the protective film may comprise at least one of a chromium compound, a silane compound, and a nitrogen compound.

[0026] The electrode according to the present invention comprises a current collector including a copper foil and an active material layer formed on at least one surface of the current collector, wherein the copper foil includes a copper film including a metal chelating agent, and the △CTE according to Formula 1 below may be 10 μm / (m·℃) or less.

[0027] [Equation 1]

[0028] △CTE = CTE2 - CTE1

[0029] In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.

[0030] A secondary battery according to the present invention comprises a negative electrode, a positive electrode, an electrolyte, and a separator interposed between the negative electrode and the positive electrode, wherein the negative electrode comprises a current collector comprising a copper foil, and the copper foil comprises a copper film comprising a metal chelating agent, and the △CTE according to Formula 1 below may be 10 μm / (m·℃) or less.

[0031] [Equation 1]

[0032] △CTE = CTE2 - CTE1

[0033] In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.

[0034] The composition for manufacturing copper foil according to the present invention may include copper ions, an inorganic acid, and a metal chelating agent.

[0035] In one embodiment of the present invention, the content of the metal chelating agent may be 0.5 ppm to 3 ppm based on the total weight of the composition for manufacturing the copper foil.

[0036] In one embodiment of the present invention, the composition for manufacturing copper foil may include a copper chelate complex. Effects of the invention

[0038] The copper foil according to the present invention comprises copper containing a metal chelating agent, thereby allowing the functional groups included in the metal chelating agent to form strong chelate bonds with copper ions. As a result, the surface uniformity of the manufactured copper film can be improved, bubble formation can be suppressed, and the difference in the coefficient of thermal expansion can be minimized even under different temperature conditions.

[0039] The copper foil according to the present invention can maintain a low and stable coefficient of thermal expansion in a battery operating environment of 30°C to 40°C. In addition, the copper foil according to the present invention satisfies a difference of 10 μm / (m·°C) or less between the coefficient of thermal expansion value in the temperature range of 30°C to 40°C and the coefficient of thermal expansion value in the temperature range of 30°C to 190°C.

[0040] As a result, delamination, microcracks, and / or lifting phenomena at the interface between the copper foil and the active material layer can be suppressed. In addition, the shape of the copper foil can be stably maintained against temperature changes and expansion stresses that occur during repeated charging and discharging inside the secondary battery. Furthermore, dimensional changes of the copper foil can be suppressed even in high-temperature environments such as lamination, roll pressing, and stacking. Accordingly, warping of the copper foil can be suppressed, and manufacturing quality in the secondary battery manufacturing process can be ensured. Brief explanation of the drawing

[0042] Figure 1 schematically shows a cross-sectional view of a copper foil according to an embodiment. Figure 2 schematically shows a cross-sectional view of a cathode according to an embodiment. Figure 3 schematically shows a cross-sectional view of a secondary battery according to an embodiment. Figure 4 schematically shows a copper foil manufacturing apparatus according to an embodiment. Specific details for implementing the invention

[0043] The structural or functional descriptions of the embodiments disclosed in this specification or application are merely illustrative for the purpose of explaining embodiments according to the technical concept of the present invention. Embodiments according to the technical concept of the present invention may be implemented in various forms other than those disclosed in this specification or application, and the technical concept of the present invention is not to be interpreted as being limited to the embodiments described in this specification or application.

[0044] Furthermore, when a component is referred to as "comprising" in this specification or application, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components. Additionally, all numerical ranges indicating physical properties, dimensions, etc., of components described in this specification or application should be understood to be modified by the term "approximately" in all cases unless specifically stated otherwise. Furthermore, "ppm" in this specification or application refers to a weight basis. Moreover, "origin" in this specification or application refers to a component, structure, or the substance itself derived from a certain substance.

[0045] Additionally, terms such as "below" or "beneath," "lower," "above," and "upper" may be used in this specification or application to facilitate the description of the relationship between one element or component and another element or component as illustrated in the drawings. Spatially relative terms should be understood as terms that include different directions of the element during use or operation in addition to the directions illustrated in the drawings. For example, if the element illustrated in the drawings is flipped, the element described as "below" or "beneath" of another element may be placed "above" of the other element. Accordingly, the exemplary term "below" may include both the lower and upper directions. Likewise, the exemplary terms "above" or "upper" may include both the upper and lower directions.

[0047] The copper foil according to the present invention, the electrode including the same, and the secondary battery are described below.

[0049] Figure 1 schematically shows a cross-sectional view of a copper foil according to an embodiment.

[0050] The copper foil (10) according to the present invention may include a copper film (11). The copper film (11) may include copper (Cu) in an amount of 99 weight % or more, 99.3 weight % or more, 99.6 weight % or more, or 99.9 weight % or more.

[0051] The copper film (11) can be formed on a rotating cathode drum through electroplating. The copper film (11) may have a shiny surface that is in direct contact with the rotating cathode drum during the electroplating process and a matte surface on the opposite side. Specifically, the copper film (11) can be formed by the copper foil manufacturing device of FIG. 4 described later.

[0052] The copper film (11) may include a metal chelating agent. A functional group included in the metal chelating agent may form a strong chelating bond with copper ions. The functional group may be an amino group and / or a hydroxyl group. The amino group and / or hydroxyl group may chelate bond with the copper ions to form a copper chelating complex. Fine grains may be uniformly formed by the copper chelating complex, thereby dispersing stress during thermal expansion of the copper film (11). The copper ions may be prevented from aggregating with impurities by the metal chelating agent, thereby suppressing the recrystallization of the copper ions and improving thermal stability. The elastic modulus of the copper foil (10) produced by the copper chelating complex may be controlled, thereby reducing the strain due to thermal expansion of the copper foil (10). The residual stress and interfacial stress on the copper foil (10) can be relieved by the copper chelate composite, so that the rate of change of the coefficient of thermal expansion can be stabilized.

[0053] The metal chelating agent may be derived from a component included in the electrolyte during the copper film (11) manufacturing process described later. The metal chelating agent may be identified by ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry), XPS (X-ray Photoelectron Spectroscopy), and / or FT-IR (Fourier transform infrared spectroscopy). The metal chelating agent may be identified by the detection of nitrogen and / or oxygen distributed around copper ions on the copper film (11) by the ToF-SIMS, XPS, and / or FT-IR. The nitrogen may be derived from the amino functional group of the metal chelating agent. The oxygen may be derived from the hydroxyl functional group of the metal chelating agent.

[0054] The above metal chelating agent may be selected from one or more of the group consisting of chitosan, carboxymethyl chitosan, acetylated chitosan, polyethyleneimine, dendrimer, triethylenetetramine, glycine, citric acid, alginic acid, and pectin.

[0055] Preferably, the metal chelating agent may be chitosan containing amine and hydroxyl groups as functional groups.

[0056] The copper foil (10) may include a protective film (12) formed on at least one surface of the copper film (11). Although the protective film (12) formed on one surface of the copper film (11) is shown in FIG. 1, the protective film (12) may be formed on both surfaces of the copper film (11).

[0057] The protective film (12) may include at least one of a chromium compound, a silane compound, and a nitrogen compound. The protective film (12) can prevent oxidation and corrosion of the copper film (11) and improve heat resistance, thereby extending the lifespan of the copper foil (10) and the lifespan of the product containing the copper foil (10).

[0058] The copper foil (10) above may have a △CTE of 10 μm / (m·℃) or less according to Formula 1 below.

[0059] [Equation 1]

[0060] △CTE = CTE2 - CTE1

[0061] In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.

[0062] The above △CTE may be an indicator representing dimensional stability according to temperature change of the copper foil (10). The above △CTE may be an indicator representing interfacial bonding stability between the copper foil (10) and the active material layer. The above △CTE may be an indicator representing heat resistance reliability in a repeated charge / discharge environment of a secondary battery including the copper foil (10). The above △CTE may be an indicator representing dimensional precision and bonding quality in high-temperature manufacturing processes such as lamination, roll pressing, and lamination using the copper foil (10).

[0063] The above △CTE can be adjusted according to whether the copper film (11) contains a metal chelating agent, the composition of the electrolyte and the content of each composition in the copper foil manufacturing process described later, and the manufacturing process conditions.

[0064] The above △CTE may be 10 µm / (m·℃) or less, 9 µm / (m·℃) or less, 8.5 µm / (m·℃) or less, or 8.1 µm / (m·℃) or less.

[0065] The above CTE1 may be 15 µm / (m·℃) ± 1 µm / (m·℃), 15 µm / (m·℃) ± 0.9 µm / (m·℃), 15 µm / (m·℃) ± 0.8 µm / (m·℃), or 15 µm / (m·℃) ± 0.7 µm / (m·℃).

[0066] The above CTE2 may be 20 µm / (m·℃) ± 4 µm / (m·℃), 20 µm / (m·℃) ± 3.8 µm / (m·℃), 20 µm / (m·℃) ± 3.5 µm / (m·℃), or 20 µm / (m·℃) ± 2 µm / (m·℃).

[0067] If the above range is satisfied, mechanical damage such as electrode bending, wrinkling, tearing, and breakage can be prevented when applied as a current collector for a secondary battery.

[0068] The copper foil (10) above may have a thermal expansion change rate index of 0.6 or less according to the following formula 2.

[0069] [Equation 2]

[0070] Thermal expansion rate of change index = △CTE / CTE1

[0071] In the above Equation 2, △CTE and CTE1 are as defined in the above Equation 1.

[0072] The above thermal expansion change rate index may be an indicator of resistance to stress and delamination at the interface of the copper foil (10). The lower the thermal expansion change rate index, the less variability there is in the coefficient of thermal expansion due to the rise in temperature, so the stress at the interface of the copper foil (10) can be relieved more, and delamination cracks can be suppressed more.

[0073] The above thermal expansion change rate index may be 0.6 or less, 0.58 or less, 0.56 or less, or 0.55 or less. When the above range is satisfied, the peeling phenomenon and interlayer separation phenomenon of the electrode including the copper foil (10) can be suppressed.

[0074] The copper foil (10) above may have a thermal expansion stability index of 3 or less according to the following formula 3.

[0075] [Equation 3]

[0076] Thermal expansion stability index (units omitted) =

[0077] In the above Equation 3, the X i is CTE1, CTE2, CTE3, CTE4, or CTE5, where μ is the average of CTE1 to CTE5, n is 5, and CTE1 and CTE2 are as defined in Equation 1, and The above CTE3 is the third coefficient of thermal expansion of the copper foil measured by increasing the temperature from 40°C to 50°C under the same conditions, the above CTE4 is the fourth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 50°C to 60°C under the same conditions, and the above CTE5 is the fifth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 60°C to 70°C under the same conditions.

[0078] The above thermal expansion stability index may be an indicator that numerically represents the deviation of the coefficient of thermal expansion of the copper foil (10) according to temperature change ranges. A lower thermal expansion stability index may indicate that the copper foil (10) maintains a constant thermal expansion behavior even in various temperature ranges. Accordingly, the above thermal expansion stability index may be an indicator representing the thermal dimensional stability of the copper foil (10).

[0079] The above thermal expansion stability index may be 3 or less, 2.8 or less, 2.5 or less, or 2 or less.

[0080] The above CTE3, CTE4, and CTE5 may be 20 µm / (m·℃) ± 5 µm / (m·℃), 20 µm / (m·℃) ± 4.5 µm / (m·℃), 20 µm / (m·℃) ± 4 µm / (m·℃), or 20 µm / (m·℃) ± 3.5 µm / (m·℃).

[0081] If the above range is satisfied, interfacial damage, peeling, or lifting phenomena can be suppressed even in a charge / discharge environment involving repeated high and low temperatures.

[0083] Figure 2 schematically shows a cross-sectional view of a cathode according to an embodiment.

[0084] The electrode according to the present invention may include a current collector comprising a copper foil (10) and an active material layer formed on at least one surface of the current collector.

[0085] The above electrode may be a negative electrode (100). The above active material layer may be a negative active material layer (15).

[0086] The copper foil (10) comprises a copper film (11) containing a metal chelating agent, and has a △CTE of 10 μm / (m· according to Formula 1 below. It may be less than.

[0087] [Equation 1]

[0088] △CTE = CTE2 - CTE1

[0089] In the above Equation 1, the CTE1 is 5 using a thermomechanical analyzer 30 at speed from 40 It is the first coefficient of thermal expansion of the copper foil measured by raising the temperature to, and the CTE2 is 30 under the same conditions from 190 This is the second coefficient of thermal expansion of the copper foil measured by raising the temperature to [level].

[0090] The copper foil (10) may include a protective film (12) formed on at least one surface of the copper film (11). The copper foil, copper film, protective film, and △CTE according to Formula 1 may be the same as the copper foil, copper film, protective film, and △CTE according to Formula 1 described above.

[0091] In FIG. 2 above, the protective film (12) and the negative active material layer (15) formed on one side of the copper film (11) are shown, but the protective film (12) and the negative active material layer (15) may be formed on both sides of the copper film (11).

[0092] The ratio of the thickness of the current collector may be 1% to 12%, 3% to 12%, 5% to 12%, or 6% to 12% relative to the total thickness of the electrode. When the above range is satisfied, the mechanical support of the negative electrode active material layer (15) can be maintained and the energy density can be improved.

[0093] The above negative electrode active material layer (15) may include a negative electrode active material.

[0094] The type of the above-mentioned negative electrode active material is not particularly limited, and compounds capable of reversible intercalation and deintercalation of lithium may be used. For example, carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, and highly crystalline carbon; and metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys, may be used. Examples of low-crystallinity carbon include soft carbon and hard carbon, while examples of highly crystalline carbon include natural graphite, kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes. The above-mentioned cathode active material may be a composite material including a metallic compound and a carbonaceous material, depending on the needs.

[0095] The above negative electrode active material can be mixed with a binder and a conductive material to form a negative electrode active material layer (15).

[0096] The bonding strength between the cathode active material and the conductive material can be improved by the above binder, and the bonding strength between the cathode active material layer (15) and the copper foil (10) can be improved.

[0097] The type of binder mentioned above is not particularly limited, but for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), fluororubber, styrene butadiene rubber (SBR), cellulose-based resin, etc. may be used.

[0098] The conductivity of the cathode active material can be improved by the above conductive material. The type of the above conductive material is not particularly limited, but, for example, Super-P, graphite, acetylene black, etc. may be used.

[0099] The above electrode may include a primer layer disposed between the copper foil (10) and the negative active material layer (15).

[0100] The interfacial adhesion between the copper foil (10) and the negative active material layer (150) can be improved by the primer layer.

[0101] The primer layer may include a thickener. The thickener may include one or more selected from the group consisting of carboxymethyl cellulose (CMC), methyl cellulose (MC), hydroxypropyl cellulose (HPC), methyl hydroxypropyl cellulose (MHPC), ethyl hydroxyethyl cellulose (EHEC), methyl ethyl hydroxyethyl cellulose (MEHEC), and cellulose gum.

[0102] The primer layer may include a binder. The binder may include one or more selected from the group consisting of styrene butadiene rubber, polyvinylidene fluoride, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, styrene monomer (SM), butadiene (BD), and butyl acrylate (BA).

[0103] The primer layer may include one or more conductive materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, metal fiber, fluorinated carbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives to improve conductivity.

[0105] Figure 3 schematically shows a cross-sectional view of a secondary battery according to an embodiment.

[0106] A secondary battery (1000) according to the present invention comprises a negative electrode (100), a positive electrode (200), an electrolyte (300), and a separator (400) interposed between the negative electrode (100) and the positive electrode (200). The negative electrode (100) comprises a current collector comprising a copper foil (10), and the copper foil (10) comprises a copper film comprising a metal chelating agent. The △CTE according to Formula 1 below may be 10 μm / (m·℃) or less.

[0107] [Equation 1]

[0108] △CTE = CTE2 - CTE1

[0109] In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 40°C at a rate of 5°C / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30°C to 190°C under the same conditions.

[0110] The above-mentioned cathode (100) and △CTE according to Equation 1 may be the same as the aforementioned cathode and △CTE according to Equation 1.

[0111] The above anode (200) may include a structure in which an anode active material layer (25) is formed on an anode current collector (20).

[0112] The anode (200) can be manufactured using general methods known in the field. For example, the anode (200) can be manufactured by mixing and stirring a solvent, binder, conductive material, and dispersant with an anode active material to prepare a slurry, then applying it to the anode current collector (20), compressing it, and drying it.

[0113] The positive current collector (20) is a highly conductive metal, and is a metal to which the slurry of the positive active material can easily adhere. It is not particularly limited as long as it has high conductivity without causing chemical changes in the secondary battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc., may be used. In addition, fine irregularities may be formed on the surface of the positive current collector to increase the adhesion of the positive active material. The positive current collector (20) may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., and may have a thickness of 3 μm to 500 μm.

[0114] The above-mentioned positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and specifically, may include a lithium composite metal oxide comprising lithium and one or more metals such as cobalt, manganese, nickel, or aluminum.

[0115] The above electrolyte (300) may be a non-aqueous electrolyte. The above electrolyte (300) may include a lithium salt and an organic solvent. The above organic solvent may include at least one of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate (MPC), dipropyl carbonate (DPC), vinylene carbonate (VC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, sulfolane, gamma-butyrolactone, propylene sulfide, or tetrahydrofuran.

[0116] The separator (400) may be configured to prevent an electrical short circuit between the cathode (100) and the anode (200) and to allow for the flow of ions. The separator (400) may include a porous polymer film or a porous nonwoven fabric. Here, the porous polymer film may be composed of a single layer or multiple layers including polyolefin-based polymers such as ethylene polymer, propylene polymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer. The porous nonwoven fabric may include high-melting-point glass fibers or polyethylene terephthalate fibers. However, it is not limited thereto, and depending on the embodiment, the separator may be a high-heat-resistant separator (CCS; Ceramic Coated Separator) including ceramic.

[0117] The contact angle between the cathode (100) and the electrolyte (300) may be 50° or less, 45° or less, 40° or less, or 10° to 50° or less. The contact angle may be measured according to ASTM D7334. When the above range is satisfied, the surface wettability of the cathode (100) is excellent, so the uniformity of the SEI (Solid Electrolyte Interphase) layer can be improved, and the initial output characteristics and lifespan stability of the secondary battery (1000) can be improved.

[0119] The composition for manufacturing copper foil according to the present invention may include copper ions, an inorganic acid, and a metal chelating agent.

[0120] The content of the metal chelating agent may be 0.5 ppm to 3 ppm, 0.8 ppm to 3 ppm, 1 ppm to 3 ppm, or 1.2 ppm to 3 ppm based on the total weight of the composition for manufacturing the copper foil. When the above range is satisfied, the uniformity of the copper foil (10) is improved, and the formation of bubbles on the surface of the copper foil (10) can be suppressed. In addition, the concentration of copper ions is uniform, so the plating speed of the copper ions can be increased, and the current efficiency of the secondary battery (1000) being manufactured can be improved.

[0121] The above composition for manufacturing copper foil may include a copper chelate complex. The copper chelate complex may be formed by chelate bonding between the copper ion and the metal chelating agent.

[0122] The above composition for manufacturing copper foil may be the same as the electrolyte described below.

[0123] Figure 4 schematically shows a copper foil manufacturing apparatus according to an embodiment.

[0124] A copper foil (10) according to the present invention can be manufactured by the above copper foil manufacturing device.

[0125] The method for manufacturing the copper foil (10) may include the step of forming a copper film (11) and the step of forming a protective film (12) on the copper film (11).

[0126] The manufacturing device for the copper foil (10) may include an electrolytic cell (30) for receiving an electrolyte (40), an anode plate (50) including a first anode plate (51) and a second anode plate (52), and a rotating cathode drum (60).

[0127] The first positive plate (51) and the second positive plate (52) may be electrically insulated.

[0128] The formation of the copper film (11) can be carried out by forming a seed layer through current flow between the first anode plate (51) and the rotating cathode drum (60), and growing the seed layer through current flow between the second anode plate (52) and the rotating cathode drum (60).

[0129] The current density provided by the first positive plate (51) and the second positive plate (52), respectively, may be 40 ASD to 130 ASD, 45 ASD to 130 ASD, 45 ASD to 125 ASD, or 45 ASD to 120 ASD. When the above range is satisfied, the formation of the negative active material layer (15) on the copper foil (10) can be smoothly performed, and sufficient adhesion between the copper foil (10) and the negative active material layer (15) can be provided.

[0130] The surface characteristics of the copper film (11) can be adjusted according to the degree of surface buffing or polishing of the rotating cathode drum (60). For example, the surface of the rotating cathode drum (60) can be polished with a polishing brush having a grit of #800 to #3000.

[0131] During the process of forming the copper film (11), the temperature of the electrolyte (40) may be maintained at 45°C to 65°C, 47°C to 65°C, 47°C to 63°C, or 47°C to 60°C. Depending on the temperature of the electrolyte (40), the size, crystal direction, and electrodeposition rate of the copper crystal grains may vary, and as a result, mechanical properties and surface roughness may be controlled.

[0132] The above electrolyte (40) may include copper ions, an inorganic acid, and an additive. The above electrolyte (40) may include chlorine. The above inorganic acid may include sulfuric acid.

[0133] The copper ion content in the above electrolyte (40) may be 70 g / L to 150 g / L, 70 g / L to 110 g / L, 70 g / L to 100 g / L, or 70 g / L to 90 g / L.

[0134] The copper ions contained in the above electrolyte (40) may be obtained by acid-washing a copper wire (Cu wire) with a purity of 99.9% or higher in 10% sulfuric acid for 10 to 20 minutes, followed by a washing process with distilled water. By the washing process, the acid-washed organic matter may be prevented from entering the above electrolyte (40). The concentration of the organic matter may be controlled by a filtration process using a medium such as diatomite or carbon.

[0135] The content of the sulfuric acid in the above electrolyte (40) may be 80 to 130 g / L, 85 to 130 g / L, 90 to 130 g / L, or 90 to 125 g / L.

[0136] The chlorine may contain chloride ions and chloride atoms. The chlorine may be used to remove silver (Ag) ions introduced into the electrolyte (40) during the process of forming the copper film (11). The chlorine may precipitate the silver ions in the form of silver chloride (AgCl). The silver chloride may be removed by filtration.

[0137] The concentration of the chlorine may be 15 ppm to 30 ppm. When the above range is satisfied, the removal of the silver ions can be carried out smoothly, and unnecessary reactions caused by an excess amount of chlorine can be suppressed.

[0138] The above additive may include the aforementioned metal chelating agent.

[0139] The above additive may include a first additive that can impart surface gloss, stress reduction, and flattening functions to the copper film (11).

[0140] The charge amount of the electrolyte (40) is increased by the first additive above, so that the electrodeposition rate of the copper ions can be increased, the curl characteristics of the copper foil (10) being manufactured can be improved, and the gloss of the copper foil (10) can be improved.

[0141] The concentration of the first additive may be 1 ppm to 20 ppm, 2 ppm to 20 ppm, 3 ppm to 20 ppm, or 3 ppm to 18 ppm. When the above range is satisfied, the surface roughness of the copper foil (10) being manufactured is maintained and the gloss may be improved.

[0142] The first additive above may include sulfonic acid or its metal salt.

[0143] The first additive may include at least one of bis-(3-sulfopropyl)-disulfide disodium salt, diethylenetriaminepenta(methylenesulfonic acid), 3-mercapto-1-propanesulfonic acid, 3-(N,N-dimethylthiocarbamoyl)-thiopropanesulfonate sodium salt, 3-[(amino-iminomethyl)thio]-1-propanesulfonate sodium salt, o-ethyldithiocarbonato-S-(3-sulfopropyl)-ester sodium salt, 3-(benzothiazolyl-2-mercapto)-propyl-sulfonic acid sodium salt, and ethylenedithiodipropylsulfonic acid sodium salt.

[0144] The above additive may include a second additive that can provide a function to reduce the electrodeposition speed and improve the uniformity of the copper film (11).

[0145] The rapid increase in roughness and decrease in strength of the copper film (11) can be prevented by the second additive above.

[0146] The concentration of the second additive may be 0.1 ppm to 20 ppm, 0.1 ppm to 15 ppm, 0.1 ppm to 12 ppm, or 1 ppm to 10 ppm. When the above range is satisfied, wrinkles and tearing of the copper foil (10) being manufactured can be prevented, and physical properties such as appearance, gloss, strength, and elongation can be maintained.

[0147] The second additive mentioned above may include a nonionic water-soluble polymer.

[0148] The second additive above may include at least one of hydroxyethylenecellulose, hydroxypropylcellulose, ethylcellulose, carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, polyethylene glycol, polyvinyl alcohol, polypropylene glycol, polyacrylamide, polyoxyethylene, polyvinylpyrrolidone, polyethylene-polypropylene copolymer, polyglycerin, polyethylene glycol dimethyl ether, stearic acid polyglycol ether, and stearyl alcohol polyglycol ether.

[0149] The above additive may include a third additive that prevents electrodeposition blockage in the fine pattern of the copper film (11) and maintains flatness.

[0150] By suppressing electrodeposition in the region of the copper film (11) where the local current density is high due to the third additive, a leveling action can be performed to make the surface of the copper film (11) flat.

[0151] The concentration of the third additive may be 1 ppm to 20 ppm, 1 ppm to 10 ppm, or 1 ppm to 9 ppm. When the above range is satisfied, the surface gloss of the copper foil (10) being manufactured is uniform, and the phenomenon of the surface roughness rapidly increasing can be suppressed.

[0152] The above third additive may include a nitrogen-containing heterocyclic quaternary ammonium salt or a derivative thereof.

[0153] The above third additive may include at least one of the compounds represented by the following chemical formulas 1 to 5.

[0154] [Chemical Formula 1]

[0155]

[0156] [Chemical Formula 2]

[0157]

[0158] [Chemical Formula 3]

[0159]

[0160] [Chemical Formula 4]

[0161]

[0162] [Chemical Formula 5]

[0163]

[0164] In the above chemical formulas 1 to 5, ℓ1 to ℓ4, m1 to m4, and n1 to n5 each represent a repeating unit, are integers greater than or equal to 1, and may be identical or different from each other.

[0165] The number average molecular weight of each of the compounds represented by the above chemical formulas 1 to 5 may be 500 g / mol to 12,000 g / mol. When the above range is satisfied, the increase in surface roughness variation may be suppressed, and the glossiness and flatness of the copper film (11) may be improved.

[0166] The compounds represented by Chemical Formulas 1 to 5 above can be prepared by polymerization or copolymerization using DDAC (Diallyl dimethyl ammonium chloride). The compound represented by Chemical Formula 1 above may be PAS-2451 (Mw 30,000 g / mol, Nittobo). The compound represented by Chemical Formula 2 above may be PAS-84 (Mw 20,000 g / mol, Nittobo). The compound represented by Chemical Formula 3 above may be PAS-2351 (Mw 25,000 g / mol, Nittobo). The compound represented by Chemical Formula 4 above may be PAS-A-1 (Mw 5,000 g / mol, Nittobo) or PAS-A-5 (Mw 4,000 g / mol, Nittobo). It may be PAS-J-81 (Mw 180,000 g / mol, Nittobo), a compound represented by the above chemical formula 5.

[0167] The above additive may include a fourth additive for controlling the growth direction of the copper film (11) and for particle refinement.

[0168] Fine grains of the copper film (11) can be induced by the above-mentioned fourth additive, and surface flattening and thermal stability can be enhanced.

[0169] The concentration of the fourth additive may be 0.5 ppm to 20 ppm, 1 ppm to 20 ppm, 2 ppm to 20 ppm, or 3 ppm to 20 ppm. When the above range is satisfied, the thermal stability and surface flatness of the copper film (11) may be improved, and the tensile strength may be enhanced.

[0170] The above-mentioned fourth additive may include a protein derivative. The protein derivative may include at least one of collagen, collagen peptide, and gelatin.

[0171] The weight-average molecular weight of the protein derivative may be 1,000 g / mol to 10,000 g / mol, 1,000 g / mol to 10,000 g / mol, 1,000 g / mol to 10,000 g / mol, or 1,000 g / mol to 10,000 g / mol. When the above range is satisfied, the surface flattening of the copper film (11) can be improved, and the occurrence of bubbles and pores on the surface of the copper film (11) due to the increase in the viscosity of the electrolyte (40) can be suppressed.

[0172] The above protein derivative may include an α-helix structure and a β-sheet structure. The α-helix structure enables stable adsorption with copper ions due to strong hydrogen bonding, and the current distribution can be uniform depending on the layered structure. The β-sheet structure is an average structure that enables wide surface area coverage, forms a porous network, allows for selective ion permeability, and enables large crystallization.

[0173] The ratio of the above α-Helix structure to the above β-Sheet structure may be 7:3 to 3:7, 6.5:3.5 to 3:7, 6.5:3.5 to 3.5:6.5, or 6:4 to 4:6. When the above range is satisfied, side reactions with chloride ions can be suppressed, thereby improving current efficiency and preventing an increase in the rate of pore formation due to the accumulation of the β-Sheet structure.

[0174] The content of hydrogen peroxide (H2O2) in the above electrolyte (40) may be 1 ml / L to 10 ml / L, 1 ml / L to 9.5 ml / L, 1 ml / L to 9.2 ml / L, or 1 ml / L to 9 ml / L.

[0175] The concentration of silver (Ag) in the above electrolyte (40) may be 0.1 ppm to 10 ppm, 0.1 ppm to 9.5 ppm, 0.1 ppm to 9 ppm, or 0.1 ppm to 8 ppm.

[0176] The concentration of cerium (Ce) in the above electrolyte (40) may be 2 ppm to 10 ppm, 2 ppm to 9.5 ppm, 2 ppm to 9 ppm, or 2 ppm to 8 ppm.

[0177] The concentration of lead (Pb) in the electrolyte (40) may be 1 ppm to 20 ppm, 1 ppm to 19 ppm, 1 ppm to 18 ppm, or 1 ppm to 15 ppm.

[0178] The concentration of molybdenum (Mo) in the above electrolyte (40) may be 25 ppm or less, 20 ppm or less, 15 ppm or less, or 0.1 ppm to 25 ppm.

[0179] The concentration of nickel (Ni) in the above electrolyte (40) may be 15 ppm to 150 ppm, 15 ppm to 130 ppm, 15 ppm to 120 ppm, or 15 ppm to 100 ppm.

[0180] The concentration of tungsten (W) in the above electrolyte (40) may be 0.3 ppm to 5 ppm, 0.3 ppm to 4.5 ppm, 0.3 ppm to 4.2 ppm, or 0.3 ppm to 4 ppm.

[0181] The concentration of cobalt (Co) in the above electrolyte (40) may be 330 ppm or less, 320 ppm or less, 300 ppm or less, or 100 ppm to 330 ppm.

[0182] The concentration of iron (Fe) in the above electrolyte (40) may be 300 ppm or less, 280 ppm or less, 250 ppm or less, or 0.1 ppm to 300 ppm.

[0183] The concentration of arsenic (As) in the above electrolyte (40) may be 0.5 ppm to 5 ppm, 0.5 ppm to 4.5 ppm, 0.5 ppm to 4.2 ppm, or 0.5 ppm to 4 ppm.

[0184] The concentrations of the above silver, cerium, lead, molybdenum, nickel, tungsten, cobalt, iron, and arsenic include all atoms present in the ions and molecules.

[0185] When the above range is satisfied, the crystal grain structure of the copper foil (10) is maintained uniformly, and the anisotropy of crystal growth is suppressed, so that the nonlinearity of the thermal expansion behavior due to temperature change can be minimized. As a result, the △CTE according to the above-mentioned Equation 1 can satisfy 10 μm / (m·℃) or less.

[0186] When forming the copper film (11), the flow rate of the electrolyte (40) supplied into the electrolytic cell (30) is 35 m 3 / hour to 46 m 3 / hour, 37 m 3 / hour to 46 m 3 / hour, 39 m 3 / hour to 46 m 3 / hour, or 41 m 3 / hour to 45 m 3 It may be / hour. If the above range is satisfied, the electrolyte (40) is filtered during the circulation process of the electrolyte (40), and solid impurities present in the electrolyte (40) can be removed while electroplating for forming the copper film (11) is performed.

[0187] The flow rate deviation of the above electrolyte (40) can be controlled to 5% or less, 4% or less, 3% or less, or 2% or less per unit time (second). When the above range is satisfied, the copper film (11) can be formed uniformly, and the weight deviation of the manufactured copper foil (10) can be minimized.

[0188] In order to remove impurities from the surface of the copper film (11), water washing may be performed in the cleaning tank. In order to remove impurities from the surface of the copper film (11), after acid cleaning is performed, water cleaning may be performed to remove the acidic solution used in the acid cleaning.

[0189] The method for manufacturing the copper foil (10) may include the step of forming a protective film (12) on the copper film (11). The copper film (11) may be immersed in an anticorrosion solution (70). When the copper film (11) is immersed in the anticorrosion solution (70), it may be guided by a guide roll placed within the anticorrosion solution (70).

[0190] The above anti-corrosion liquid (70) may include at least one of a chromium compound, a silane compound, and a nitrogen compound. When forming the protective film (12) on the copper film (11), a method of immersing the copper film (11) in a potassium dichromate solution of 1 g / L to 10 g / L at room temperature for 1 second to 30 seconds may be implemented. The protective film (12) may include a silane compound by silane treatment and a nitrogen compound by nitrogen treatment. A copper foil (10) may be manufactured by forming the protective film (12).

[0192] The present invention will be described in more detail below based on examples and comparative examples. However, the following examples and comparative examples are merely illustrative for further explaining the present invention, and the present invention is not limited by the following examples and comparative examples.

[0194] Examples

[0195] Example 1

[0196] A copper foil was manufactured using a foil making machine comprising an electrolytic cell (30), a rotating cathode drum (60) disposed in the electrolytic cell (30), and an anode plate (50) disposed spaced apart from the rotating cathode drum (60).

[0197] The electrolyte (40) is a copper sulfate solution, the copper ion concentration in the electrolyte (40) is 87 g / L and the sulfuric acid concentration is 110 g / L, the temperature of the electrolyte (40) is 55 ℃ and the current density is 60 ASD (A / dm²). 2 It was set to ). In addition, the chlorine (Cl) concentration contained in the electrolyte (40) was maintained at 20 ppm.

[0198] The above electrolyte (40) contained 10 ppm of bis-(3-sulfopropyl)-disulfide disodium salt (SPS), 5 ppm of polyethylene glycol (PEG), and 5 ppm of collagen (Mw 5,000 g / mol). In addition, the above electrolyte (40) contained 2 ppm of chitosan as a metal chelating agent.

[0199] A copper film (11) was manufactured by applying a current at a current density of 60 ASD between the rotating cathode drum (60) and the anode plate (50). Afterward, the copper film (11) was immersed in an anti-corrosion solution (70) for about 2 seconds. The anti-corrosion solution (70) had chromic acid as its main component, and the concentration of the chromic acid was 5 g / L.

[0200] Afterwards, a copper foil (10) with a thickness of 6 μm was manufactured by chromate treatment on both sides of the copper film (11) to form a protective film.

[0202] Examples 2 to 5 and Comparative Examples 1 to 5

[0203] Copper foil was manufactured under the same process conditions as Example 1, except that the main composition of the electrolyte and the content of each composition listed in Table 1 below were applied and the thickness of the copper foil being manufactured was controlled.

[0205] division Copper ion concentration (g / L) Sulfuric acid concentration (g / L) Chlorine (ppm) SPS(ppm) PEG(ppm) Collagen (ppm) Metal chelating agent (ppm) Copper foil thickness (㎛) Example 1 87 110 20 10 5 5 2 6 Example 2 87 110 20 10 5 5 1.5 6 Example 3 87 110 20 10 5 5 3 6 Example 4 87 110 20 10 5 5 1.5 6 Example 5 87 110 20 10 5 5 2 8 Comparative Example 1 87 110 20 10 5 - - 6 Comparative Example 2 87 110 20 10 5 - - 8 Comparative Example 3 87 110 20 10 5 10 - 6 Comparative Example 4 87 110 20 10 5 10 0.2 6 Comparative Example 5 87 110 20 10 5 10 10 6

[0207] Experimental Example

[0208] Experimental Example 1 - Coefficient of Thermal Expansion

[0209] Each copper foil sample prepared in Examples 1 to 5 and Comparative Examples 1 to 5 was prepared. For each of the samples, a thermomechanical analyzer (Seiko Exstar 6000) was used in accordance with ASTM E-831 under conditions of a nitrogen atmosphere and a 60 mN load to measure the first coefficient of thermal expansion by increasing the temperature from 30 ℃ to 40 ℃ at a rate of 5 ℃ / min. Separately, the second coefficient of thermal expansion was measured by increasing the temperature from 30 ℃ to 190 ℃ under the same conditions, and the results are shown in Table 2 below.

[0210] The above coefficient of thermal expansion was calculated by the following equation.

[0211] [ceremony]

[0212] coefficient of thermal expansion = ΔL / [L O Х ΔT]

[0213] In the above formula, the above L O is the initial length (m) of the sample, ΔL is the change in length (㎛) of the sample, and ΔT is the change in temperature (℃).

[0215] Experimental Example 2 - Electrode Bending Evaluation

[0216] An active material slurry was applied to each copper foil prepared in Examples 1 to 5 and Comparative Examples 1 to 5. The active material slurry was prepared by mixing 2 parts by weight of styrene-butadiene rubber (SBR) and 2 parts by weight of carboxymethylcellulose (CMC) with respect to 100 parts by weight of graphite. The active material slurry was uniformly applied onto the copper foil using a roll-to-roll method and in the Machine Direction (MD) direction, and then dried. The application amount of the active material slurry was approximately 16 mg / cm². 2 The thickness was about 100 µm.

[0217] After the above active material slurry is dried, a roll press process is carried out under conditions of a roll gap of 6 μm, a speed of 1 m / min, a linear pressure of 1,000 kgf / cm, and a pressurization of 2,500 kg, so that the density is approximately 1.5 g / cm³ 3 An electrode with a phosphorus active material layer formed thereon was manufactured.

[0218] Each of the above-manufactured electrodes was cut to a size of 10 cm × 10 cm and placed horizontally on a glass plate. Subsequently, the height of the four corners of the electrode was measured, and the average value was calculated as the bending value of the electrode. After the bending value was measured for each side of the electrode, the larger of the two values ​​was used as the final bending value of the electrode. If the electrode bent by more than 5 mm on one side, it was evaluated as defective, and the results are shown in Table 2 below.

[0220] Experimental Example 3 - Evaluation of Wrinkle and / or Tearing Occurrence

[0221] During the cathode manufacturing process in Experimental Example 2 above, the occurrence of wrinkles and / or tearing of the copper foil was observed visually. It was evaluated according to the following criteria, and the results are shown in Table 2 below.

[0222] - Good: No wrinkles or tears occurred on the copper foil

[0223] - Defect: Wrinkles or tears occurred on the copper foil

[0225] Experimental Example 4 - Evaluation of Fracture Occurrence

[0226] For each negative electrode prepared in Experimental Example 2 above, a metal lithium foil with a thickness of 0.4 mm was used as the counter electrode (anode). A polypropylene sheet with a thickness of 0.1 mm was used as the separator, and a coin-type half-cell was prepared by using an electrolyte in which LiPF61M was dissolved in a solvent mixed with ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7.

[0227] Each of the above coin-type half-cells was charged with a constant current of 0.1C until the voltage reached 0.01V, and the process of discharging with a constant current of 0.1C until the voltage reached 1.5V was performed three times to stabilize the battery.

[0228] Subsequently, each of the above coin-type half-cells was charged with a constant current of 0.5C until the voltage reached 0.01V, and discharged with a constant current of 0.5C until the voltage reached 1.0V, a process of 500 cycles was performed. After 500 charge-discharge cycles, the fracture of the negative electrode contained in the coin-type half-cell was observed. It was evaluated according to the following criteria, and the results are shown in Table 2 below.

[0229] - ○: No fracture occurred at the cathode

[0230] - ×: Fracture occurred at the cathode

[0232] Experimental Example 5 - Evaluation of Current Efficiency

[0233] After the charge-discharge experiment of each coin-type half-cell manufactured in Experimental Example 4 above, the current efficiency was measured according to the following formula. The experiment was conducted for a total of 10 cycles, and the current efficiency for each cycle from the 2nd cycle to the 10th cycle, excluding the initial 1st cycle, was measured. Subsequently, the average value of the measured current efficiency was evaluated according to the following criteria, and the results are shown in Table 2 below.

[0234] - Excellent: Current efficiency 99.5% or higher

[0235] - Suitable: Current efficiency 99% or higher

[0236] - Non-compliant: Current efficiency less than 99%

[0238] division CTE1 1) (㎛ / (m·℃) CTE2 2) (㎛ / (m·℃) △CTE 3) (㎛ / (m·℃) Electrode bending evaluation Assessment of wrinkle and / or tear occurrence Fracture occurrence assessment Current efficiency evaluation Example 1 15.1 20.9 5.8 Good Good ○ excellence Example 2 15.7 20.0 4.3 Good Good ○ excellence Example 3 15.6 23.7 8.1 Good Good ○ excellence Example 4 14.5 18.6 4.1 Good Good ○ excellence Example 5 15.1 21.9 6.8 Good Good ○ excellence Comparative Example 1 10.5 28.7 18.2 error Good × Non-conforming Comparative Example 2 9.7 27.2 17.5 error Good × Non-conforming Comparative Example 3 9.8 22.5 12.7 Good error ○ fitness Comparative Example 4 10.7 23.1 12.4 error Good × fitness Comparative Example 5 14.2 24.7 10.5 Good Good ○ Non-conforming 1) CTE1: First coefficient of thermal expansion 2) CTE2: Second coefficient of thermal expansion 3) △CTE: CTE2 - CTE1

[0240] According to Tables 1 and 2 above, the copper foil according to Examples 1 to 5 contains a metal chelating agent, and the ΔCTE is controlled to be 10 μm / (m·℃) or less.

[0241] It was confirmed that the uniformity of the copper film is improved due to the formation of such a copper chelate complex, thereby improving current efficiency, and due to the stable thermal expansion coefficient maintenance characteristic, mechanical damage such as electrode bending, wrinkling, tearing, and fracture does not occur when applied as a current collector in a secondary battery. Explanation of the symbols

[0243] 10: Copper foil 11: Copper film 12: Shield 15: Cathode active material layer 20: Positive current collector 25: Positive active material layer 30: Electrolyzer 40: Electrolyte 50: Positive plate 51: First positive plate 52: Second positive plate 60: Rotating cathode drum 70: Anti-corrosion solution 100: Cathode 200: Anode 300: Electrolyte 400: Separator 1000: Secondary battery

Claims

Claim 1 Copper foil comprising a copper film containing a metal chelating agent, wherein the metal chelating agent comprises one or more selected from the group consisting of chitosan, carboxymethyl chitosan, and acetylated chitosan, and has a △CTE of 10 μm / (m·℃) or less according to Formula 1 below: [Formula 1] △CTE = CTE2 - CTE1 In Formula 1 above, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 40℃ at a rate of 5℃ / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 190℃ under the same conditions. Claim 2 In claim 1, the copper foil having a CTE1 of 15 μm / (m·℃) ± 1 μm / (m·℃). Claim 3 In claim 1, a copper foil having a thermal expansion change rate index of 0.6 or less according to the following Equation 2: [Equation 2] Thermal expansion change rate index = △CTE / CTE1 In the above Equation 2, △CTE and CTE1 are as defined in the above Equation 1. Claim 4 In claim 1, copper foil having a thermal expansion stability index of 3 or less according to the following Equation 3: [Equation 3] Thermal expansion stability index (unit omitted) = In the above Equation 3, the x i is CTE1, CTE2, CTE3, CTE4, or CTE5, where μ is the average of CTE1 to CTE5, n is 5, and CTE1 and CTE2 are as defined in Equation 1, and The above CTE3 is the third coefficient of thermal expansion of the copper foil measured by increasing the temperature from 40°C to 50°C under the same conditions, the above CTE4 is the fourth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 50°C to 60°C under the same conditions, and the above CTE5 is the fifth coefficient of thermal expansion of the copper foil measured by increasing the temperature from 60°C to 70°C under the same conditions. Claim 5 In claim 4, the copper foils CTE3, CTE4, and CTE5 are 20 μm / (m·℃) ± 5 μm / (m·℃). Claim 6 In claim 1, the copper foil comprises a protective film formed on at least one surface of the copper film, and the protective film comprises at least one of a chromium compound, a silane compound, and a nitrogen compound. Claim 7 A current collector comprising a copper foil; and an electrode comprising an active material layer formed on at least one surface of the current collector, wherein the copper foil comprises a copper film comprising a metal chelating agent, and the metal chelating agent comprises one or more selected from the group consisting of chitosan, carboxymethyl chitosan, and acetylated chitosan, and the electrode having a △CTE of 10 μm / (m·℃) or less according to the following Equation 1: [Equation 1] △CTE = CTE2 - CTE1 In the above Equation 1, CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 40℃ at a rate of 5℃ / min using a thermomechanical analyzer, and CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 190℃ under the same conditions. Claim 8 A secondary battery comprising a negative electrode; a positive electrode; an electrolyte; and a separator interposed between the negative electrode and the positive electrode, wherein the negative electrode comprises a current collector comprising a copper foil, the copper foil comprises a copper film comprising a metal chelating agent, and the metal chelating agent comprises one or more selected from the group consisting of chitosan, carboxymethyl chitosan, and acetylated chitosan, and the △CTE according to the following Formula 1 is 10 μm / (m·℃) or less: [Formula 1] △CTE = CTE2 - CTE1 In Formula 1, the CTE1 is the first coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 40℃ at a rate of 5℃ / min using a thermomechanical analyzer, and the CTE2 is the second coefficient of thermal expansion of the copper foil measured by increasing the temperature from 30℃ to 190℃ under the same conditions. Claim 9 A composition for manufacturing copper foil comprising copper ions; inorganic acid; a nonionic water-soluble polymer; a protein derivative; and a metal chelating agent, wherein the metal chelating agent comprises one or more selected from the group consisting of chitosan, carboxymethyl chitosan, and acetylated chitosan. Claim 10 A composition for manufacturing copper foil according to claim 9, wherein the content of the metal chelating agent is 0.5 ppm to 3 ppm based on the total weight of the composition for manufacturing copper foil. Claim 11 In claim 9, the copper foil manufacturing composition comprises a copper chelate complex formed by the chelate bonding of the copper ions and the metal chelating agent.

Citation Information

Patent Citations

  • Easily Handleable Electrolytic Copper Foil, Electrode Comprising The Same, Secondary Battery Comprising The Same, and Method for Manufacturing The Same

    KR1020180040754A

  • Electrolytic copper foil having high-temperature dimensional stability and texture stability, and manufacturing method therefor

    WO2019151719A1

  • Electrolytic Copper Foil Capable of Preventing Defects of curl, Tear or Wrinkle Thereof, Electrode Comprising The Same, Secondary Battery Comprising The Same, and Method for Manufacturing The Same

    KR1020220096493A